Promotion effect of metal phosphides towards electrocatalytic and photocatalytic water splitting. Issue 3 (22nd March 2021) - Han, Yanling; Chen, Yong; Fan, Rongli; Li, Zhaosheng; Zou, Zhigang
Abstract: Hydrogen evolution from water splitting over semiconductors has been considered one of the most promising ways to address energy shortages and environmental pollution. Searching for low‐cost, highly efficient, and durable catalysts is the key to improve the hydrogen production rate. Expensive noble metals, such as Pt and Au, are generally loaded onto semiconductors to promote photocatalytic activity. Metal phosphides are promising candidates to replace noble metals in hydrogen generation via electrocatalytic or photocatalytic water splitting due to their low hydrogen‐producing overpotential, tunable electronic structure, high electrical conductivity, and low price. In this review article, the characteristics and synthetic methods of metal phosphides are briefly introduced, and the development of metal phosphides for electrocatalytic or photocatalytic water splitting is presented. Finally, the challenges and future directions of metal phosphides are discussed. Abstract : In this article, the characteristics, the synthetic methods, and the development of metal phosphides are introduced. Besides, the challenges and future directions of metal phosphides are discussed.